Study The Effect of Steam Injection on Gas Turbine Performance - Reyad Qaddoura; Nuri Eshoul (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
This study aims to evaluate the impact of steam injection technology on the performance of the Siemens SGT5-2000E gas power plant in western Tripoli, Libya, using the ASPEN Plus software for performance analysis. The results showed that steam injection increased efficiency by 52.55% and enhanced electrical power output by 53.5% compared to the conventional plant. Specific fuel consumption decreased by 34.76%, while CO₂ emissions were reduced by 34.73%. An analysis of the effect of ambient air temperature (ranging from 15°C to 45°C) revealed that efficiency dropped by 1.3% for every 5°C increase without steam injection, whereas the drop was only 0.9% with steam injection. Regarding specific fuel consumption, it increased by 1.58% without the technology and by 1.01% with it. For CO₂ emissions, the increase was 1.58% without using the technology and 1.01% with its application. Additionally, an availability analysis was conducted to evaluate the system’s effectiveness. The results indicated that steam injection technology contributes to improving the overall availability of the plant by reducing exergy losses and enhancing combustion stability, leading to better performance under varying operating conditions.